Massive haemoperitoneum with lifesaving autotransfusion following ruptured ectopic pregnancy in a low-resource setting: a case report - Kubeyinje, Weyinmi E.; Iweka, Reuben O.; Anthony, Uwadiae (International Surgery Journal, 2026)
Ectopic pregnancy is a potentially life-threatening obstetric emergency characterised by implantation of the fertilised ovum outside of the uterine cavity. It remains a leading cause of maternal morbidity and mortality. Ruptured ectopic pregnancy can cause massive intra-abdominal bleeding requiring urgent surgery. Survival after a very large haemoperitoneum is rare, especially in low-resource settings where rapid resuscitation and surgical care may be limited. This case is being reported due to the massive haemorrhage and the good outcome. We report the case of a 27-year-old woman who presented with symptoms suggestive of early pregnancy and severe anaemia. Transvaginal ultrasound revealed a normal non-gravid uterus with no intrauterine gestational sac and a complex left adnexal mass. There was significant intraperitoneal fluid extending to the pouch of Douglas and Morrison’s pouch, suggesting haemoperitoneum exceeding 1500 ml. The patient subsequently deteriorated and was diagnosed with a ruptured left tubal ectopic pregnancy. Emergency laparotomy revealed approximately 6.5 litres of haemoperitoneum and a ruptured left ampullary ectopic pregnancy. Left total salpingectomy was performed, and autotransfusion of 5 litres was carried out. Postoperative management included intravenous fluids, antibiotics, analgesics, and close monitoring. Massive haemoperitoneum resulting from ruptured ectopic pregnancy is associated with a high risk of hypovolemic shock and maternal mortality, particularly in settings where diagnosis and intervention may be delayed. Most reported cases involve smaller volumes of intraperitoneal bleeding, as patients often deteriorate before such extensive blood loss occurs. The survival of this patient despite massive haemoperitoneum is therefore remarkable. This outcome underscores the critical role of early recognition, rapid resuscitation, and prompt surgical intervention in the management of ruptured ectopic pregnancy. It also highlights the potential benefit of supportive measures such as blood transfusion and autotransfusion in managing severe haemorrhage. Reporting such rare survivals contributes to the existing literature by demonstrating that favourable outcomes are achievable even in extreme presentations when timely and appropriate management is instituted. This case highlights the importance of early diagnosis and prompt surgical management of ectopic pregnancy to prevent life-threatening complications. Strengthening early pregnancy evaluation and improving access to ultrasound services can significantly reduce maternal morbidity and mortality associated with ruptured ectopic pregnancy.